2 Assessing splenic switch-off in adenosine stress CMR for patients with atrial fibrillation: a propensity matched study. (1st November 2021) - Barrishi, Adam; Graby, John; Khavandi, Ali; Dastidar, Amardeep; Rodrigues, Jonathan
Abstract : Background: Stress cardiac magnetic resonance imaging (CMR) is a valuable investigation in the functional assessment of coronary artery disease. The phenomenon of splenic switch-off is a validated indicator of adequate vasodilator stress unique to adenosine vasodilator stress CMR. Patients in atrial fibrillation (AF) may have a reduced adenosine response due to a lower hyperaemic coronary flow reserve. Thus, we hypothesised that patients in AF would achieve splenic switch-off less frequently than those in sinus rhythm (SR). Methods: 1100 adenosine stress CMR studies were retrospectively identified from a prospectively maintained clinical CMR database over a 5-year period (2016–2021). 71 patients in AF on ECG at the time of CMR were identified. The SR cohort was drawn by propensity score matching to the AF group for age, sex, and body mass index. The adenosine dose administered, symptoms, and heart-rate change observed during infusion and scan result were recorded. Splenic switch-off was evaluated subjectively through visual assessment and semi-quantitatively via changes in splenic and myocardial signal intensity from rest to stress. Multivariate logistic regression analysis assessed for predictors of splenic switch-off. Results: 70 AF patients were matched to 70 in SR (mean age: 72±8 years vs 72±9 years, p=0.96;%male: 86% vs 84%, p=0.81). Subjective splenic switch-off occurred significantly less frequently in AF than in SR (34/70 [49%] vs 53/70 [76%], p=0.003). Objective assessment supported this, with a smaller splenic signal intensity difference between stress and rest in AF vs SR (median splenic stress:rest peak signal intensity ratio 0.92 [IQR, 0.61–1.11] vs 0.56 [IQR, 0.45–0.75], p<0.001). A heart-rate increase over 10bpm in response to adenosine was a significant predictor of visual splenic switch-off in SR patients but not in AF patients. Fewer AF patients had inducible ischaemia than SR patients (9/70 [13%] vs 17/69 [25%], p=0.058). However, this difference was not driven by inducible ischaemia rates between AF and SR patients who did not achieve splenic switch-off (6/36 [17%] vs 4/17 [24%], p=0.403). Conclusions: In this retrospective propensity matched study, splenic switch-off occurred significantly less frequently in patients with AF. This may risk the under-diagnosis of inducible ischaemia, but requires further assessment.